The Effectiveness of Hydrotherapy-Halliwick Concept in Children With Juvenile Idiopathic Arthritis: Assessment and Treatment. Issue 2 (May 2021) - Karastamati, Christina; Chandolias, Konstantinos; Grammatikou, Georgios; Hristara-Papadopoulou, Alexandra
Abstract : Introduction: The main symptoms of juvenile idiopathic arthritis (JIA) include swelling of the affected joints, sensitivity, painful movement restriction, and walking disorders. A wealth of findings and research is available on the benefits of various physiotherapy interventions. Instead, there are a small number of studies that examine the benefits of more alternative forms of physiotherapy such as hydrotherapy and more specifically the Halliwick therapy. In the hydrotherapy studies so far, the results are equivalent to classical physiotherapy and sometimes better. Aim: This study attempts to record and highlight the effect of the Halliwick hydrotherapy in children with JIA in a 2-month intervention program. In particular, it focuses on (1) balance and (2) plantar pressure distribution before and after the intervention. Methodology: The methodology we used to collect our data was quantitative research, and the research tools used were the Berg balance scale and a modular platform system to measure plantar pressure. The sample consisted of 16 children with JIA who took measurements before and after the intervention. The duration of this intervention was 2 months. Data analysis was performed using the SPSS v21 statistical program. Results: Some remarkable results were obtained: (1) all subjects had no significant change in the already good balance; and (2) all subjects had a significant improvement in the uniform distribution of plantar pressure following the Halliwick treatment sessions. Conclusions: The philosophy of the Halliwick hydrotherapy is a more alternative form of physical therapy that has been shown to contribute to improving the distribution of weight and plantar pressure in children suffering from JIA.